Masa Kerja dan Shift Kerja Berhubungan Dengan Stres Kerja Pada Perawat Instalasi Rawat Inap Di Rsud Dr. H. Chasan Boesoirie Ternate Maluku Utara Tahun 2022 - Salsabila, Nurul Qalbi; Situngkir, Decy; Millah, Izzatu; Kusumaningtiar, Devi Angeliana; Sangadji, Namira Wadjir; Rusdy, Mirta Dwi Rahmah (Mulawarman University, 2023)
Background and objectives: According to a survey by the American Nurses Association (ANA), more than 34% of nurses assess their emotional health as not, or not at all, emotionally healthy. The results of a survey conducted by PPNI in 2018 stated that 50.9% of nurses in Indonesia experienced work stress. The causes of work stress are workload, such as targets, interpersonal relationships, with superiors or other co-workers. This study aims to analyze the factors associated with stress in the inpatient nurse at RSUD Dr. H. Chasan Boesoirie Ternate North Maluku in 2022. Methods: This type of research uses a quantitative method with a cross sectional study design. The population in this study were 179 nurses at the inpatient installation of RSUD Dr. H. Chasan Boesoirie Ternate, North Maluku. With a sample size of 81 nurses at the inpatient installation of RSUD Dr. H. Chasan Boesoirie Ternate, North Maluku. Data analysis using the Chi Square Test. This research was conducted in September 2022 – February 2023. Research Results: The univariate results found that the highest prevalence was nurses who experienced high work stress (77.8%), high workload (54.3%), years of service at risk category ( 76.5%), shift work at risk category (74.1%), and age category at risk (51.9%). Conclusion: There is a relationship between work period and work shifts with work stress in nurses at the inpatient installation of RSUD Dr. H. Chasan Boesoirie Ternate, North Maluku.Keywords: Work Stress; Nurse; Workload; Years of service; Shift work; Age.